Whiteness, Normal Theory, and Disability Studies - Phil Smith (Disability Studies Quarterly, 2004)
Analogies can be drawn between social cartographies of disability and the landscape of race. Understanding these analogies can benefit understandings of both disability and race. Contrary to modernist understandings, disability, like race, is plural, socially constructed, founded on hidden ideologies, and a direct function of global capitalism. Deconstructing racism by postmodern critical theorists has led to the development of whiteness theories, which portray whiteness as a raced category that is chromatically absent to Whites, an unexamined and unexplored normative backdrop. As a result of this exploration of the terrain of whiteness, taxonomies of difference are seen to be created by processes of discrimination, rather than the other way around. For too long, constructions of race and disability have been conflated by the eugenic practices of modernist science. Whiteness underlies the oppression of people with disabilities. Disability studies scholars can learn much about disability and ableism by proposing a corollary to whiteness theories, that is, normal theories, as a way to unpack and dismantle the unspoken language of normative ideologies that create disability as a social category.